DNAzymes and ribozymes carrying 2'-C-methyl nucleotides - Pontiggia, Rodrigo Martin (2008)
DNAzymes and Ribozymes find applications as inhibitors of gene expression and in detection systems such as biosensors, among others. In particular, we are interested in the properties of hammerhead ribozymes carrying 2′-C-methylnucleotides and 10–23 DNAzymes containing (2′R) or (2′S)- 2′-C-methyl 2′-deoxynucleotides. In this work a new synthesis of 2′-C-Methyluridine phosphoramidite is presented. Special emphasis is dedicated to the improvement of the protection of the tertiary 2′-hydroxyl group. Comparison to previous protecting strategies as well as the stability under oligonucleotide synthesis conditions is discussed. 2′-C-methyl-2′-deoxynucleosides show differential preferred conformations depending on the configuration of the 2′-carbon. The influence of these modifications on the activity of 10–23 DNAzymes is also assessed.